Healthcare providers' preconception care practice and associated factors in Ethiopia: a systematic review and meta-analysis - Zeleke, Agerie Mengistie; Tassew, Worku Chekol; Assefa, Getaw Wubie; Ferede, Yeshiwas Ayale (Frontiers in Health Services, 2025)
IntroductionProviding preconception care through good practice by healthcare providers is very important in reducing maternal and child mortality and morbidity. However, there are no available detailed review articles in Ethiopia. Therefore, the purpose of this study was to ascertain the level of knowledge of preconception care and related factors among Ethiopian healthcare providers.MethodsA variety of data sources, such as PubMed, Scopus, African Journal Online (AJOL), Google Scholar, and Semantic Scholar, were used to identify studies published until March 2023. This review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The data were subsequently transferred to STATA software version 11 for further data analysis. A random-effects model was used to estimate the prevalence of practice about preconception care, and the results are reported in a forest plot.ResultsEight studies involving 3,848 healthcare providers were included. The pooled prevalence of a good level of practice of preconception care among healthcare providers in Ethiopia was 53.54 (95% CI: 45.09, 61.98), p < 0.0001. Healthcare providers who had a degree and above educational status (AOR = 4.83; 95% CI: 1.80, 12.96), those working at hospital health facilities (AOR = 2.97; 95% CI: 2.07, 4.27), those ever reading preconception care guidelines (AOR = 3.49; 95% CI: 2.39, 5.07), availability of libraries at health facilities (AOR = 5.59; 95% CI: 2.84,11.04), trained healthcare providers on HIV counseling and testing (AOR = 6.86; 95% CI: 3.75, 12.53), and trained healthcare providers on preconception care (AOR = 6.19; 95% CI: 4.23, 9.06) were predictors of a good level of practice with preconception care.ConclusionsNearly half of healthcare providers do not have good practice of preconception care in Ethiopia. Therefore, healthcare providers' knowledge of preconception care should be improved through preconception care, HIV counseling and testing training, and access to guidelines, libraries, and the internet at nearby health facilities, especially at health centers. Finally, stakeholders collaborate with policymakers to develop strategies to improve healthcare providers' preconception care practice.